EVALUASI PROGRAM APLIKASI GRESIKPEDIA DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN GRESIK - Kurniawati, Mega; Prastyawan, Agus (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The Gresikpedia application program is a priority program for the Regent of Gresik Nawakarsa who is incorporated into Karsa One, namely Gresik AKAS. The purpose of this research is to describe the Evaluation of the Gresikpedia Application Program at the Communication and Informatics Office of Gresik Regency. The research focus is based on program evaluation indicators according to Bridgman and Davis including: Input, Process, Outputs, Outcomes. This type of research is qualitative descriptive approach. Observation data collection techniques, interviews, documentation. Results. input, which has not been implemented optimally, lies in the aspect of human resources and aspects of supporting infrastructure. The process has not been implemented optimally, because the aspect of effectiveness does not yet have an SOP for managing the Gresikpedia application and the aspect of efficiency is that many people do not know about the Gresikpedia application program. Outputs have not been implemented optimally because the number of Gresikpedia application downloads has not met the predetermined target. Outcomes, carried out optimally, because the positive impact aspects of the Gresikpedia application program have been felt by the community and the negative aspects of obstacles can still be overcome. Suggestion: Input, add human resources to manage the CCTV sub menu, the Gresikpedia program manager can simplify, more flexible the rules for granting permission to upload information with added features. Process, making SOPs for managing the Gresikpedia application, as well as the need for a guidebook for using the Gresikpedia application, conducting socialization evenly to the wider community, it is necessary to make video tutorials for using the Gresikpedia application to be distributed via YouTube, other social media and during direct socialization. Outputs, evaluate and determine the target downloader every month. Keywords: Program Evaluation,Public Services,Electronic Government